Predictors of Early Discontinuation of Pegylated Interferon for Reasons Other Than Lack of Efficacy in United States Veterans With Chronic Hepatitis C. (November 2015) - LaFleur, Joanne; Hoop, Robert; Korner, Eli; DuVall, Scott; Morgan, Timothy; Pandya, Prashant; Han, Jian; Knippenberg, Kristin; Nelson, Richard E.
Abstract : During the dual-therapy era, many patients with chronic hepatitis C discontinued therapy for reasons other than lack of efficacy (non-LOE). We determined whether selected patient characteristics predicted non-LOE discontinuation using national databases of U.S. veterans with Genotypes 1–4. We identified U.S. veterans in the Veterans Health Administration system in 2004–2009 who had hepatitis C-confirming RNA laboratory results and initiated therapy with pegylated interferon and ribavirin. We used a rule to classify patients who discontinued pegylated interferon early, based on pharmacy refill and viral response data. Multivariate Cox regression was used to identify predictors of non-LOE discontinuation. Of 321, 238 patients with a hepatitis C International Classification of Diseases, Ninth Revision, code, 15, 297 (4.8%) met all inclusion criteria. Non-LOE discontinuers comprised 30.3% of patients. For Genotypes 1–4, the predictors (adjusted hazard ratio) of greatest magnitude were comorbidities of myocardial infarction/congestive heart failure (1.36), renal disease (1.34), and platelets 100/mm 3 or more (1.38). For Genotypes 2 and 3, predictors of greatest magnitude were Black race (1.30), myocardial infarction/congestive heart failure (1.84), albumin 3.5 mg/dl or more (1.65), sleep aid use (1.32), and poor persistence with antidepressants (1.31) and antihypertensive agents (1.37). Our study suggests that many host factors may have contributed to non-LOE dual-therapy discontinuation in veterans and may possibly predict non-LOE discontinuation in triple therapy.